2021
DOI: 10.1242/dmm.048913
|View full text |Cite
|
Sign up to set email alerts
|

Joint development recovery on resumption of embryonic movement following paralysis

Abstract: Fetal activity in utero is a normal part of pregnancy and reduced or absent movement can lead to long-term skeletal defects such as Fetal Akinesia Deformation Sequence (FADS), joint dysplasia and arthrogryposis. A variety of animal models with decreased or absent embryonic movements show a consistent set of developmental defects providing insight into the aetiology of congenital skeletal abnormalities. At developing joints defects include reduced joint interzones with frequent fusion of cartilaginous skeletal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 70 publications
(87 reference statements)
0
11
0
Order By: Relevance
“…Our data reveal a very dramatic mechanically-engendered inhibition of longitudinal growth in hydrogel, suggesting that prolonged static compressive loads may evoke an irreversible blockade of EO. Studies in chick embryos have shown that the effects of 'rigid' paralysis at early embryo stages, which would likewise engender quasi-static load, could be partially overcome in the spine, but not in developing joints, by restoring movement [16]. This suggests that the dynamic loads associated with movement may reverse some of the effects of quasi-static loading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data reveal a very dramatic mechanically-engendered inhibition of longitudinal growth in hydrogel, suggesting that prolonged static compressive loads may evoke an irreversible blockade of EO. Studies in chick embryos have shown that the effects of 'rigid' paralysis at early embryo stages, which would likewise engender quasi-static load, could be partially overcome in the spine, but not in developing joints, by restoring movement [16]. This suggests that the dynamic loads associated with movement may reverse some of the effects of quasi-static loading.…”
Section: Discussionmentioning
confidence: 99%
“…Specific connections between endochondral growth and local mechanical stimuli are emerging. Mechanical stimuli have, for example, been shown to regulate cartilage growth [9][10][11], and animal models in which movement is restricted show impaired growth [12][13][14][15][16]. Despite these connections, the candidate regulators through which mechanical factors interact to control endochondral growth are ill-defined.…”
Section: Introductionmentioning
confidence: 99%
“…Insights on cartilage mechanoregulation can be gained by studying the effects of mechanical loads on cartilage in vivo/in ovo, cartilage explants ex vivo or chondrocytes in vitro. In vivo [5], in ovo [4,9] and in vitro [20] studies have shown that the development of functioning joints depends on the timing and duration of movement. While early movements, prior to joint cavitation (the physical separation .…”
Section: Introductionmentioning
confidence: 99%
“…It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted February 10, 2023. ; https://doi.org/10.1101/2023.02.09.527957 doi: bioRxiv preprint of the skeletal elements), are crucial for the separation of joint elements [4,5,7,9,12,15], short periods of immobility after cavitation has taken place have only minor influence on joint morphology [4]. However, long periods of immobilisation, even after cavitation has occurred, result in marked shape changes which can lead to joint fusion in most extreme cases in chick limbs [4,9,12] and larval zebrafish jaws [5,7,15]. Fetal chick knees cultured in vitro showed that the duration of loading is an important factor influencing joint growth and morphogenesis, with longer durations resulting in more normally developed joints [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation